2014
DOI: 10.1002/pd.4416
|View full text |Cite
|
Sign up to set email alerts
|

Can the quantity of cell‐free fetal DNA predict preeclampsia: a systematic review

Abstract: Cell-free fetal DNA quantification is a promising marker for preeclampsia prediction, especially for the development of early-onset or severe preeclampsia. However, because of the heterogeneity in published studies, a precise conclusion about the statistical and clinical relevance cannot be made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
48
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 72 publications
(164 reference statements)
0
48
0
2
Order By: Relevance
“…It has been shown that the placenta is the major source of circulating cell-free fetal nucleic acids in maternal plasma (5)(6)(7). Significantly elevated levels of total cell-free DNA and selected placenta-specific RNA transcripts have also been reported in the maternal plasma of women with PE (8)(9)(10)(11), restricted fetal growth (12), and preterm birth (13)(14)(15), supporting a role for cell-free nucleic acids as a noninvasive tool for placental monitoring. Previous studies have attempted to provide a comprehensive assessment of maternal plasma nucleic acids by microarray analysis, massively parallel transcriptomic, or methylomic sequencing (16)(17)(18)(19)(20)(21)(22).…”
mentioning
confidence: 94%
“…It has been shown that the placenta is the major source of circulating cell-free fetal nucleic acids in maternal plasma (5)(6)(7). Significantly elevated levels of total cell-free DNA and selected placenta-specific RNA transcripts have also been reported in the maternal plasma of women with PE (8)(9)(10)(11), restricted fetal growth (12), and preterm birth (13)(14)(15), supporting a role for cell-free nucleic acids as a noninvasive tool for placental monitoring. Previous studies have attempted to provide a comprehensive assessment of maternal plasma nucleic acids by microarray analysis, massively parallel transcriptomic, or methylomic sequencing (16)(17)(18)(19)(20)(21)(22).…”
mentioning
confidence: 94%
“…46 Cell-free fetal DNA cfDNA and cffDNA are also probable combined biomarkers of PE, mainly due to their sensitivity and specificity in biological fluids. 47,48 The identification of the methylated RASSF1A promoter gene, which is elevated in early-PE pregnancies, [49][50][51] offers a promising alternative to the quantification of cffDNA, using Y-chromosome-specific sequences. 52 Notably, high doses of human cffDNA did not induce PE-like symptoms in a murine in vivo model, 53 reinforcing the notion that the increase in RASSF1A methylation is a consequence rather than a cause of PE.…”
mentioning
confidence: 99%
“…[76][77][78] However, conclusions about clinical applicability are limited by the heterogeneity in study design, PE definition, and gestational ages at blood draw and/ or approaches used. For example, inclusion of cases of late-onset PE or preexisting hypertension may increase heterogeneity of etiology.…”
Section: Preeclampsiamentioning
confidence: 98%